Analisis Usaha Pembibitan Kakao di Kabupaten Pesawaran Provinsi Lampung, Indonesia (Studi Kasus pada UD. Thamrin Ikhsan) - Anggita Dwi Oktaviani; Marbudi Marbudi; Varingan Prianando Tambunan; Abu Hasan As-Sadili; Shinta Triadisti; Poppy Antika Sari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Cocoa (Theobroma cacao L) is an important commodity crop widely cultivated in tropical regions, including Indonesia. In recent years, cocoa production in Pesawaran Regency, Lampung Province, has declined significantly, partly due to the use of low-quality seedlings. This study aims to analyze the cocoa nursery business in Pesawaran Regency, particularly at UD Thamrin Ikhsan, a cacao nursery that has been operating since 2012. The analytical methods used in this study include cost-benefit analysis, R/C ratio, and B/C ratio to evaluate the business feasibility. The results show that the average total cost per seedling is IDR 2,799, while the profit per cocoa seedling is IDR 4,201. The R/C ratio of 2.50 and the B/C ratio of 1.50 indicate that every IDR 1 spent generates substantial revenue and profit. Based on these ratio values, which are greater than 1, it can be concluded that the cocoa seedling business at UD Thamrin Ikhsan is feasible to continue and further develop.